Activities of the wintering party at Syowa Station by the 29th Japanese Antarctic Research Expedition in 1988-1989 - Okitsugu Watanabe (National Institute of Polar Research, 1991)
The wintering party of the 29th Japanese Antarctic Research Expedition perfomed its activities at two wintering sites from 1988 to 1989,consisting of 27 members at Syowa Station (69°00′S, 39°35′E)(leader : Okitsugu WATANABE) and 10 members at Asuka Station (71°31.5′S, 24°8.3′E)(leader : Keizo YANAI). Scientific and logistics activities at both wintering stations are reported separately. Wintering activities at Asuka Station have already been reported by K. YANAI (Nankyoku Shiryo, 34,394,1990). The main scientific research programs at Syowa Station were as follows : 1) Development of unmanned geophysical observatory (upper atmosphere physics). 2) Clouds and precipitation observation by means of vertical radar carried out as a part of Antarctic Climate Research Program (ACR)(lower atmosphere physics). 3) Biological investigation of Antarctic terrestrial ecosystem (biological science), part of international Biological Investigations of Terrestrial Antarctic Systems (BITAS). Routine and fundamental geoscience were performed as in preceding years.